Improving Islamic Religious Education Learning Outcomes Utilizing the Brain-based Learning Model Based on Students' School Origin and Cognitive Stage - Somantri, Enjang Aris; Sabarudin, Mohammad; Al Ayyubi, Ibnu Imam; Suryana, Irfan; Singh, W. C. (Indonesian Journal of Islamic Education Studies (IJIES), 2024)
This study aims to improve learning outcomes in Islamic religious education (IRE) utilizing the brain-based learning model based on students' school origin and cognitive stage. This study used a quantitative approach and was conducted in SMPN 1 Wanayasa Purwakarta Regency with a sample of 31 students, SMPN 2 Parongpong West Bandung Regency with a sample of 32 students, and SMPN 2 Ciampel Karawang Regency with a sample of 37 students. The research instrument was a test with data analysis requirements, consisting of a normality test and a homogeneity test, using Kolmogorov-Smirnov and Shapiro-Wilk, assisted by SPSS software version 26. It was found that there were significant differences and interactions in the IRE learning outcomes that utilized the brain-based learning model based on students' school origin in SMPN 1 Wanayasa, SMPN 2 Parongpong, and SMPN 2 Ciampel, and students' cognitive stages in the concrete, transitional, and formal categories. Therefore, further study can be carried out based on students' school origin at the Senior High School level and cognitive stage utilizing the brain-based learning model.